A Comprehensive Catalog of Emission-line Nebulae, Star Clusters, and Supergiants in M31 from the LAMOST Spectroscopic Survey - Pinjian Chen; Bingqiu Chen; Xuan Fang; Haibo Yuan; Baisong Zhang; Xiangwei Zhang; Jiarui Sun; Xiaowei Liu (The Astronomical Journal)
Spectroscopic observations of various tracers in nearby galaxies, such as Andromeda (M31), play a crucial role in identifying and classifying individual stellar populations and nebular objects, thereby enhancing our understanding of galactic composition, environment, and dynamics, as well as stellar evolution. While the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) survey of M31 has produced extensive data sets, a comprehensive catalog of emission-line nebulae, star clusters, and supergiants is yet to be completed. In this paper, we present a final catalog of 384 emission-line nebulae, 380 star clusters, and 375 supergiants and candidates in M31, as carefully selected and identified from the LAMOST spectroscopic database. These objects were classified using a random forest algorithm, followed by thorough visual examinations of their spectral characteristics, as well as morphologies revealed by archive images. For emission-line nebulae, we measured radial velocities and relative fluxes of emission lines, enabling further classification of planetary nebulae and H ii regions. Additionally, we identified 245 emission-line nebulae in M33. This work lays the data foundation for the study of M31 and offers valuable tracers to investigate M31’s structure and evolution.